Response Of Growth And Production Of Cucumber Plants (Cucumis Sativus L.) On The Administration Of Potassium Silica And Cow Manure - Halawa, Rahmat Iman; Kurniawan, Dedi; Nadhira, Ahmad (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
This research was carried out at the UPTD BIH Gedung Johor, Medan Johor, Medan City, starting from December 2023 to February 2024. This research aims to determine the effect of cucumber plant growth and production on the provision of potassium silica and cow manure. This research used a factorial randomized block design (RAK) with 2 treatment factors. The first factor is potassium silica with the symbol (K) which consists of 3 treatment levels, namely: Ko = Without potassium silica 0-gram polybag, Ki = 2.5 cc/ liter of water, K2 = 5 cc/ liter of water. The second factor is cow manure with the symbol (S) which consists of 4 treatment levels, namely: So = No fertilizer, S = 100 grams/polybag, S2 200 grams polybag, and S: = 300 grams/polybag. The parameters observed in this study were plant length (cm), number of leaves (strands), flowering age (days), number of fruit per plant (fruit), weight of fruit per plant (kg), number of fruit per plot (fruit), weight of fruit per plot (kg). The results of the research showed that Potassium Silica treatment had a significant effect on flowering age, and the number of fruit per plot, and had a very significant effect on fruit weight per plot. Providing cow manure fertilizer had no significant effect on all parameters. The best fruit weight per plot was obtained in the K0S2 combination, namely 2.13 kg. Kata kunci : Kalium Silika, Pupuk Kandang, Mentimun.